2018
DOI: 10.3892/ol.2018.8962
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 regulates ANO6 to promote migration of pancreatic ductal adenocarcinoma cells via the ERK signaling pathway

Abstract: The increase in migratory ability of pancreatic ductal adenocarcinoma cells is a key event in the development of metastasis to the lymph nodes and distant organs. Although the C-C motif chemokine receptor 7 (CCR7) and its ligand, C-C motif chemokine ligand 21 (CCL21), have been revealed to serve an important role in tumor migration, their precise roles and potential underlying mechanisms remain largely unknown. The present study revealed that overexpression of CCR7 significantly promoted BxPC-3 cell migration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Given that intracellular alkalization is one of the hallmarks of cancer cells (Cardone, Casavola and Reshkin, 2005; White, Grillo-Hill and Barber, 2017) and TMEM16F is highly expressed in a wide spectrum of tumors (Jacobsen et al ., 2013; Wang et al ., 2018; Xuan, Wang and Xie, 2019), we next sought to examine whether endogenous TMEM16F in tumor cells can also be strongly promoted by intracellular alkalization as we observed in the HEK293 cells exogenously expressed with TMEM16F. To address this, we utilized a human choriocarcinoma cell line BeWo that highly expresses TMEM16F CaPLSases to enable cell-cell fusion of the placental trophoblast tumor cells (Zhang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that intracellular alkalization is one of the hallmarks of cancer cells (Cardone, Casavola and Reshkin, 2005; White, Grillo-Hill and Barber, 2017) and TMEM16F is highly expressed in a wide spectrum of tumors (Jacobsen et al ., 2013; Wang et al ., 2018; Xuan, Wang and Xie, 2019), we next sought to examine whether endogenous TMEM16F in tumor cells can also be strongly promoted by intracellular alkalization as we observed in the HEK293 cells exogenously expressed with TMEM16F. To address this, we utilized a human choriocarcinoma cell line BeWo that highly expresses TMEM16F CaPLSases to enable cell-cell fusion of the placental trophoblast tumor cells (Zhang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…TMEM16F has been identified in a wide variety of cancer cells; and according to the Human Protein Atlas (http://www.proteinatlas.org), the high expression level of TMEM16F is associated with the overall prognosis of a number cancers including breast and cervical cancers. Although it is unclear how TMEM16F contributes to tumor growth and cancer progression, it has been reported that genetic manipulations of TMEM16F can change cancer cell proliferation and migration (Jacobsen et al ., 2013; Wang et al ., 2018; Xuan, Wang and Xie, 2019). Interestingly, loss of membrane phospholipid asymmetry is a salient feature of many cancerous cells, whose cell surfaces display an elevated amount of PS (Riedl et al ., 2011; Zhao et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, GO and REACTOME pathway analyses were used to investigate the interactions of these DEGs. Increasing evidence shows that LAPTM4B [52], CEACAM6 [53], SERPINE2 [54] and VNN1 [55], SPHK1 [56], HRG (histidine rich glycoprotein) [57], VEGFC (vascular endothelial growth factor C) [58], ANXA3 [59], APOA2 [60], LCN2 [61], TIMP1 [62], CD63 [63], CD151 [64], MAL2 [65], ARNTL2 [66], PKD2 [67], E2F1 [68], MMP1 [69], CCR7 [70], NOTCH2 [71], BTLA (B and T lymphocyte associated) [72], TFRC (transferrin receptor) [73], CD4 [74], ATM (ATM serine/threonine kinase) [75], LEF1 [76], CSF1R [77], CTSB (cathepsin B) [78], DUSP2 [79] and NR4A1 [80] are closely associated with progression of PDAC. PTGER3 [81] and MAGI2 [82] are linked with angiogenesis, chemoresistance, cell proliferation and migration in ovary cancer, but these genes might be liable for growth PDAC.…”
Section: Discussionmentioning
confidence: 99%